Moisture-resistant fluoride red phosphor and its preparation and application and white light LED device

By coating the CMgF3 layer on the surface of the fluoride red phosphor to form a core-shell structure, the existing fluoride red phosphor has solved the problem of poor moisture resistance, and significantly improved its luminous performance in a water environment.

CN116656347BActive Publication Date: 2025-02-28HEFEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310161936.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-02-28
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

The existing Mn4+ activated fluoride red phosphor has poor moisture resistance, which leads to the formation of black MnO2 after contacting water and oxygen, reducing the luminous efficiency.

Method used

CMgF3 is used as the waterproof layer to form an A2B1-xF6:xMn4+ core-shell structure with a surface coated CMgF3 was formed. The coating was completed in the CHF2 aqueous solution by co-precipitation method to improve the moisture resistance of the phosphor.

Benefits of technology

The moisture resistance of fluoride red phosphor is significantly improved. The absorption rate, internal quantum efficiency and external quantum efficiency of the phosphor that is not soaked in water are maintained at more than 98.15%, 96.55% and 94.8%. After soaking in water for 24 hours, it still maintains high luminous performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116656347B_ABST
    Figure CN116656347B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of inorganic non-metallic photoelectric functional materials, and discloses moisture-resistant fluoride red phosphor, preparation and application thereof, and white light LED devices. The fluoride red phosphor has a core-shell structure; the core is Mn 4+ Doped fluoride red phosphor, chemical formula A2B 1‑x F6:xMn 4+ , wherein A is at least one of Li, Na, K, Rb and Cs, B is at least one of Ti, Si, Ge, Zr and Sn, 0≤x≤0.4; the shell is a cubic perovskite compound, the chemical formula is CMgF3, wherein C is at least one of Li, Na, K, Rb and Cs. The present invention uses the generated CMgF3 as a wrapping waterproof layer to form an A2B coated with CMgF3 on the surface 1‑x F6:xMn 4+ The core-shell structure overcomes the moisture resistance problem of fluoride red powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic non-metallic photoelectric functional materials, and more specifically, relates to moisture-resistant fluoride red phosphor and its preparation and application and use as display backlight source and white light LED device. Background Art

[0002] At present, liquid crystal displays mainly use white light LEDs as backlight sources. This type of white light LED is mainly made of blue light LED chips and red and green phosphors. For white light LED devices used in display backlight sources, the narrower the phosphor emission spectrum, the more conducive it is to improving the display color gamut and color contrast, making the display more vivid and bright.

[0003] In order to meet the needs of liquid crystal display and high-end lighting applications, many scholars have developed Mn 4+ Activated fluoride system red phosphor. Mn 4+ The activated fluoride red phosphor can be effectively excited by the blue light emitted by the LED chip, and has the advantages of narrow-band red light emission, high quantum efficiency, good thermal stability, and simple synthesis method. 4+ The forbidden transition of dd orbital electrons can emit narrow-band spectrum, which can well meet the application of display. The fluoride system has low phonon energy and high energy conversion efficiency. 4+ The activated fluoride system red phosphors mainly include fluorosilicate (K 2 、Na 2 、KNa、Ba、Zn)SiF 6 :Mn 4+ , fluorogermanate (Na 2 , K 2 ,Ba)GeF 6 :Mn 4+ , Fluorostanate (K 2 、Na 2 , Cs 2 )SnF 6 ·H 2 O:Mn 4+ and fluorotitanate (K 2 、Na 2 ,Cs,Ba)TiF 6 :Mn 4+ etc. 2 SiF 6 :Mn 4+ and K 2 F 6 :Mn 4+ Both materials have been commercialized. 4+The key technical problem of activated fluoride red phosphors is poor moisture resistance. 4+ Activating Mn in the lattice of fluoride red phosphors 4+ After contacting with water and oxygen in the environment, a layer of black MnO is generated on the surface of the phosphor. 2 , greatly reducing the luminous efficiency of the phosphor. In order to overcome this technical difficulty, it is urgent to develop a technical means to improve the moisture resistance of fluoride red phosphor, or to develop a high-efficiency fluoride red phosphor with moisture resistance.

[0004] In order to make the material waterproof, people often use some inorganic and organic coatings. Using this idea, researchers have made many attempts to improve the waterproof performance of phosphors. There are currently two main surface modification methods.

[0005] One is to build a core-shell structure, coating the surface of the phosphor with a layer of inorganic or organic matter to isolate water molecules in the environment. For example:

[0006] The literature (Zhou Y.Y., et al., ACS Appl. Mater. Interfaces 2018, 10, 880–889) reported that 2 TiF 6 :Mn 4+ (KTF) phosphor surface attached with a layer of octadecyltrimethoxysilane (ODTMS), dispersed in water for 2 hours, retaining 84.3% of the initial luminescence intensity;

[0007] Literature (Li Y.L., et al., J. Lumin., 2021, 234, 117968) in K 2 SiF 6 :Mn 4+ (KSF) surface is coated with a layer of Mn-free 4+ K 2 SiF 6 Raw materials, forming KSF@K 2 SiF 6 The core-shell structure, after being immersed in water for 300 min, the luminescence intensity remained 88% of the initial intensity;

[0008] The literature (Fang M.H., et al., ACS Appl. Mater. Interfaces, 2018, 10, 29233-29237) uses oleic acid (OA) as a bridge to form KTF@OA@SiO on the surface of KTF. 2 Double-layer core-shell structure, with good water resistance;

[0009] Literature (Fang Z.Y., et al., Int. J. Appl. Ceram. Technol, 2021, 18, 1106-1113) Coating SrF on the surface of KTF 2 As a waterproof layer, the literature (Yu Y., et al., Ceram. Int., 2021, 47, 33172-33179) coated CaF on the surface of KSF 2 As a waterproof layer;

[0010] Literature (Dong Q.Z., et al. Mater. Res. Bull., 2019, 115, 98-104) Coating CaF on the surface of KTF 2 As a waterproof layer, it significantly improves the moisture resistance of the phosphor.

[0011] Another method is surface modification, which uses reducing acid or ion exchange to reduce the Mn content on the surface of phosphor particles. 4+ concentration to prevent the browning effect. For example:

[0012] The literature (Wan P.P., et al., Chem. Eng. J., 2021, 426, 131350.) and the literature (Luo P.L., et al., Chem. Eng. J., 2022, 435, 134951) adopted the method of surface passivation and ion exchange, and used the strategy of reduction-assisted surface recrystallization for surface reconstruction. After boiling, the quantum efficiency (QE) was 96.68%;

[0013] The literature (Zhou Y.Y., et al., ACS Appl. Mater. Interfaces, 2019, 6, 1802006) uses H 2 O 2 Perform surface passivation;

[0014] The literature (Liu Y., et al., Ceram. Int., 2022, 46, 18281-18286) also uses H 2 O 2 The surface of fluoride phosphor is passivated to greatly improve the moisture resistance of the phosphor.

[0015] Although these technologies can improve the waterproof performance to a certain extent, they still cannot completely overcome the moisture resistance problem of fluoride red powder. There is still an urgent need to find new water-resistant surface materials and develop new surface coating technologies. Summary of the invention

[0016] The purpose of the present invention is to address the deficiencies of the prior art and to provide a moisture-resistant fluoride red phosphor and its preparation and application as well as a white light LED device used as a display backlight source. 3 As a waterproof layer, forming a surface-coated CMgF 3 A 2 B 1-x F 6 :xMn 4+ The core-shell structure overcomes the moisture resistance problem of fluoride red powder.

[0017] In order to achieve the above-mentioned object, the first aspect of the present invention provides a moisture-resistant fluoride red phosphor, which has a core-shell structure;

[0018] Core is Mn 4+ Doped fluoride red phosphor, chemical structure is A 2 B 1-x F 6 :xMn 4+ , wherein A is at least one of Li, Na, K, Rb and Cs, B is at least one of Ti, Si, Ge, Zr and Sn, 0≤x≤0.4;

[0019] The shell is a cubic perovskite compound with a chemical formula of CMgF 3 , wherein C is at least one of Li, Na, K, Rb and Cs.

[0020] According to the present invention, preferably, the molar ratio of the shell to the core is 0.005-1.0.

[0021] In the present invention, as a preferred embodiment, the Mn 4+ The doped fluoride red phosphor was prepared by means of secondary crystallization assisted ion exchange.

[0022] The second aspect of the present invention provides a method for preparing the moisture-resistant fluoride red phosphor, comprising the following steps:

[0023] S1: Configure CHF 2 Aqueous solution and Mg(NO 3 ) 2 An aqueous solution, wherein C is at least one of Li, Na, K, Rb and Cs;

[0024] S2: The Mn 4+ Doped fluoride red phosphor with the CHF 2 The aqueous solutions are mixed and stirred uniformly to obtain a mixed solution;

[0025] S3: Continue stirring the mixed solution to mix the Mg(NO 3 )2 The aqueous solution is dripped into the mixed solution, and after the dripping is completed, stirring, solid-liquid separation, washing and drying are performed in sequence to obtain a surface-coated CMgF 3 A 2 B 1-x F 6 :xMn 4+ Core-shell structure fluoride red phosphor;

[0026] S4: Covering the surface with CMgF 3 A 2 B 1-x F 6 :xMn 4+ The core-shell structure fluoride red phosphor is immersed in water, and subjected to solid-liquid separation, washing and drying to obtain the moisture-resistant fluoride red phosphor.

[0027] According to the present invention, preferably, the CHF 2 The molar concentration of the aqueous solution is 0.001-10 mol / L.

[0028] According to the present invention, preferably, the Mg(NO 3 ) 2 The molar concentration of the aqueous solution is 0.001-10 mol / L.

[0029] According to the present invention, preferably, the CHF 2 aqueous solution, the Mg(NO 3 ) 2 The aqueous solution and the Mn 4+ The dosage ratio of the doped fluoride red phosphor is (0.01-30)L: (0.01-10)L: 1g.

[0030] According to the present invention, preferably, the Mn 4+ The molar amount of the doped fluoride red phosphor is 0.001-0.40 mol.

[0031] According to the present invention, preferably, in step S2, the stirring rate is 50-1200 rpm, and the stirring time is 0-60 min.

[0032] According to the present invention, preferably, in step S3,

[0033] The stirring rate for continuous stirring is 50-1200 rpm;

[0034] The stirring rate after the dripping is 50-1200 rpm, and the stirring time is 0-60 min;

[0035] The dripping rate is 1-90 seconds / drop.

[0036] In the present invention, the solid-liquid separation method includes suction filtration, and the washing includes repeatedly washing the filter cake with ethanol until it becomes neutral.

[0037] According to the present invention, preferably, in step S4, the soaking time is 1-60 hours.

[0038] In the present invention, as a preferred embodiment, the coating process of the present invention is in a potassium bifluoride solution, Mg 2+ , K + With F - Ions in K 2 TiF 6 :Mn 4+ KMgF is formed on the surface of phosphor particles. 3 Precipitation and coating of the entire phosphor particle to form a waterproof layer to block the [MnF 6 ] 2+ The groups are exposed to moisture in the environment, thus greatly improving the moisture resistance of the phosphor. 2 TiF 6 :Mn 4+ @KMgF 3 The phosphor was immersed in water for 24 hours. The KMgF 3 The shell layer recrystallizes in water to form a K with regular surface morphology and water resistance. 2 TiF 6 :Mn 4+ @KMgF 3 Phosphor. Figure 1 As shown:

[0039] (1) K 2 TiF 6 :Mn 4+ The phosphor and potassium bifluoride solution were mixed and stirred for 30 minutes to obtain a mixed solution;

[0040] (2) Continuously stirring the mixed solution, the Mg(NO 3 ) 2 The aqueous solution is dripped into the mixed solution at a constant dripping rate. 3 Slow growth in K 2 TiF 6 :Mn 4+ After the addition, the phosphor particles were stirred for 30 min, solid-liquid separated, washed and dried (70 ° C) to obtain K 2 TiF 6 :Mn 4+ @KMgF 3 Phosphor, the surface morphology is irregular spherical, Figure 1 ②;

[0041] (3) The K 2 TiF 6 :Mn 4+ @KMgF 3 The phosphor was immersed in water for 24 hours. The KMgF 3 After recrystallization in water, the surface morphology becomes relatively regular and smooth, such as Figure 1 ③, through solid-liquid separation, washing and drying, the moisture-resistant fluoride red phosphor is obtained.

[0042] The third aspect of the present invention provides the use of the moisture-resistant fluoride red phosphor as the red light part of a white light LED device used as a display backlight source.

[0043] A fourth aspect of the present invention provides a white light LED device used as a display backlight source, the white light LED device comprising a red light portion, a green light portion and a blue light portion;

[0044] The red light part is the moisture-resistant fluoride red phosphor.

[0045] According to the present invention, preferably, the green light part is a green phosphor with an emission wavelength peak of 520-560nm and a half-width not exceeding 35nm, preferably β-SIALON green powder; and the blue light part is an InGaN blue light chip.

[0046] The beneficial effects of the technical solution of the present invention are as follows:

[0047] The present invention adopts a simple coprecipitation method to obtain 2 The coating is completed in aqueous solution, which reduces the amount of hydrofluoric acid used and the harm of synthesis, and the generated CMgF 3 As a waterproof layer, forming a surface-coated CMgF 3 A 2 B 1-x F 6 :xMn 4+ The core-shell structure has a simple coating process, is environmentally friendly, saves resources, and is suitable for large-scale industrial applications.

[0048] The Mn without water soaking 4+ The absorption rate, internal quantum efficiency and external quantum efficiency of the doped fluoride red phosphor are 71.22, 83.48 and 59.47%, and after being immersed in water for 24 hours, they still maintain 98.15%, 96.55% and 94.8% of the initial value. The moisture-resistant fluoride red phosphor prepared by the present invention still has good luminescence performance when immersed in pure water. 3 A 2 B 1-x F6 :xMn 4+ The absorptivity, internal quantum efficiency and external quantum efficiency of the core-shell structured fluoride red phosphor are 72.56, 86.46 and 62.73%.

[0049] The present invention is based on A 2 B 1-x F 6 :xMn 4+ Fluoride red powder is used as the core and CMgF is used as the surface coating material. The coated phosphor is soaked in an aqueous solution for a long time and then filtered out for use. This process completely overcomes the problem of Mn 4+ Activated fluoride blush is afraid of moisture.

[0050] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0052] Figure 1 The K provided by Example 1 of the present invention is shown 2 TiF 6 :Mn 4+ @KMgF 3 Schematic diagram of the preparation process (coating process and recrystallization process) of phosphor (where “KTF@KMgF 3 ” is K 2 TiF 6 :Mn 4+ @KMgF 3 ).

[0053] Figure 2 The surface of Example 1 of the present invention is coated with KMgF 3 K 2 TiF 6 :Mn 4+ A photo of the core-shell structured fluoride red phosphor immersed in water for 24 hours.

[0054] Figure 3 The different coating ratios K of Examples 1-5 of the present invention are shown. 2 TiF 6 :Mn 4+ @KMgF 3 XRD spectrum of phosphor. (“2Theta(°)” indicates the XRD scanning angle, the same below)

[0055] Figure 4 The different coating ratios K of Examples 1-5 of the present invention are shown. 2 TiF 6 :Mn 4+ @KMgF 3 Emission spectrum of the phosphor after being immersed in water for 24 hours.

[0056] Figure 5 The different coating ratios K of Examples 1-5 of the present invention are shown. 2 TiF 6 :Mn 4+ @KMgF 3 Excitation spectrum of the phosphor after being immersed in water for 24 hours.

[0057] Figure 6 The different soaking times K of Examples 1, 6-9 of the present invention are shown. 2 TiF 6 :Mn 4+ @KMgF 3 XRD spectrum of phosphor.

[0058] Figure 7 (a), (c), (e), and (g) show the uncoated K in Example 1. 2 TiF 6 :Mn 4+ SEM image of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 SEM image of K of Example 1 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 SEM image of K of Example 1 after immersion in water for 60 hours 2 TiF 6 :Mn 4+ @KMgF 3 SEM image of .

[0059] Figure 7 (b), (d), (f), and (h) show the uncoated K in Example 1. 2 TiF 6 :Mn 4+ EDS spectrum of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 EDS spectrum of Example 1 immersed in water for 24 hours 2 TiF 6 :Mn4+ @KMgF 3 EDS spectrum and K of Example 1 immersed in water for 60 hours 2 TiF 6 :Mn 4+ @KMgF 3 EDS spectrum. Among them, Mn Kα1 indicates that the excited electrons in the L layer outside the nucleus of the Mn element jump to the K layer, lose energy, and release the characteristic X-ray signal, indicating that the energy spectrometer detects the signal of the Mn element; Mg Kα1_2 indicates that the excited electrons in the L layer outside the nucleus of the Mg element jump to the K layer, lose energy, and release the characteristic X-ray signal, indicating that the energy spectrometer detects the signal of the Mg element.

[0060] Figure 8 The different soaking times K of Examples 1, 6-9 are shown. 2 TiF 6 :Mn 4+ @KMgF 3 Emission spectrum of phosphor.

[0061] Fig. 9 The different soaking times K of Examples 1, 6-9 are shown. 2 TiF 6 :Mn 4+ @KMgF 3 Excitation spectrum of phosphors.

[0062] Fig.10 The emission spectra of samples of Examples 10-17 of the first orthogonal experiment are shown.

[0063] Fig.11 The emission spectra of samples of Examples 18-25 of the first orthogonal experiment are shown.

[0064] Fig.12 The emission spectra of samples of Examples 10-17 from the second orthogonal experiment are shown.

[0065] Fig.13 The emission spectra of samples of Examples 18-25 from the second orthogonal experiment are shown.

[0066] Fig.14 The different coating ratios K of Examples 26-30 are shown. 2 SiF 6 :Mn 4+ @KMgF 3 XRD spectrum of phosphor. (“KSF@KMgF 3 ” is K 2 SiF 6 :Mn 4+ @KMgF 3)

[0067] Fig.15 (a)-(f) show the uncoated K of Example 26 2 SiF 6 :Mn 4+ SEM images ((a)-(b)), K of Example 26 2 SiF 6 :Mn 4+ @KMgF 3 SEM images ((c)-(d)), K of Example 26 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 SEM images of (e)-(f)).

[0068] Fig.16 The different coating ratios K of Examples 26-30 are shown. 2 SiF 6 :Mn 4+ @KMgF 3 Emission spectrum of the phosphor after being immersed in water for 24 hours.

[0069] Fig.17 The different coating ratios K of Examples 26-30 are shown. 2 SiF 6 :Mn 4+ @KMgF 3 Excitation spectrum of the phosphor after being immersed in water for 24 hours.

[0070] Fig.18 The different coating ratios K of Examples 31-35 are shown. 2 TiF 6 :Mn 4+ @NaMgF 3 XRD spectrum of phosphor.

[0071] Fig.19 The different coating ratios K of Examples 31-35 are shown. 2 TiF 6 :Mn 4+ @NaMgF 3 Emission spectrum of the phosphor after being immersed in water for 24 hours.

[0072] Fig. 20 The different coating ratios K of Examples 31-35 are shown. 2 TiF 6 :Mn 4+ @NaMgF 3 Excitation spectrum of the phosphor after being immersed in water for 24 hours.

[0073] Fig.21 (a) shows the K of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 Packaged white LED spectra and devices.

[0074] Fig.21 (b) shows a comparison diagram of the CIE color gamut diagram of the white light LED device of Example 36 and the standard color gamut of the National Television Committee (USA). (Wherein, NTSC is the standard color gamut of the National Television Committee; Intensity is intensity, and Wavelength is wavelength)

[0075] Fig. 22 It shows that the K 2 TiF 6 :Mn 4+ (①), K 2 TiF 6 :Mn 4+ @KMgF 3 However, K after not soaking in water (②) and after soaking in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 (③) Thermal steady-state luminous flux attenuation curve of the packaged white light LED device.

[0076] Fig.23 It shows that the K 2 TiF 6 :Mn 4+ (①), K 2 TiF 6 :Mn 4+ @KMgF 3 However, K after not soaking in water (②) and after soaking in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 (③) Thermal steady-state voltage decay curve of the packaged white light LED device.

[0077] Fig.24 The surface of Example 1 is coated with KMgF 3 K 2 TiF 6 :Mn 4+ XRD spectrum of core-shell structured fluoride red phosphor.

[0078] Fig.25 Shows K 2 TiF 6 :Mn4+ @CaF 2 With K 2 TiF 6 :Mn 4 XRD spectrum of .

[0079] Fig.26 Shows K 2 TiF 6 :Mn 4+ @SrF 2 With K 2 TiF 6 :Mn 4 XRD spectrum of . DETAILED DESCRIPTION

[0080] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0081] In the following embodiments:

[0082] Mn 4+ The doped fluoride red phosphor was prepared by means of secondary crystallization assisted ion exchange;

[0083] KF 2 Purchased from Shanghai Sanaisi Reagent Co., Ltd., analytical grade AR, 99%;

[0084] Mg(NO 3 ) 2 6H 2 O was purchased from Tianjin Damao Chemical Reagent Factory, analytical grade AR, 99%;

[0085] Anhydrous ethanol was purchased from Sinopharm Chemical Reagent, analytical grade AR, 99.7%.

[0086] Example 1

[0087] This embodiment provides a moisture-resistant fluoride red phosphor, K 2 TiF 6 :Mn 4+ @KMgF 3 , the fluoride red phosphor has a core-shell structure;

[0088] K 2 TiF 6 :Mn 4+ , where Mn 4+ The doping concentration is x = 0.08;

[0089] Shell is KMgF 3 .

[0090] The molar ratio of the shell to the core (coating ratio) is 0.2.

[0091] The preparation method of the above-mentioned moisture-resistant fluoride red phosphor comprises the following steps:

[0092] S1: Prepare 2mol / L KHF 2 Aqueous solution and 1 mol / L Mg(NO 3 ) 2 An aqueous solution, wherein C is at least one of Li, Na, K, Rb and Cs;

[0093] S2: The above K 2 TiF 6 :Mn 4+ (molar weight is 0.01 mol) and 20 mL of KHF 2 The aqueous solutions were mixed and stirred (400 rpm) for 30 min to obtain a mixed solution;

[0094] S3: Continue stirring (400 rpm) the mixed solution to mix the Mg(NO 3 ) 2 The aqueous solution was dripped into the mixed solution (60 seconds / drop), and after the dripping was completed, the mixture was stirred (400 rpm) for 30 min, filtered, washed with anhydrous ethanol until neutral, and dried (70°C) to obtain a surface-coated KMgF 3 K 2 TiF 6 :Mn 4+ Core-shell structure fluoride red phosphor;

[0095] S4: coating the surface with KMgF 3 K 2 TiF 6 :Mn 4+ The core-shell structure fluoride red phosphor is immersed in water for 24 hours (such as Figure 2 As shown), after suction filtration, washing and drying (70° C.), the moisture-resistant fluoride red phosphor is obtained.

[0096] Embodiment 2-5

[0097] Examples 2-5 provide a moisture-resistant fluoride red phosphor.

[0098] K 2 TiF 6 :Mn 4+ @KMgF 3 ,

[0099] The difference between Example 2-5 and Example 1 is that the shell KMgF 3 With nuclear K 2 TiF 6 :Mn 4+ The molar ratios (coating ratios) are 0.4, 0.6, 0.8, and 1.0, respectively.

[0100] like Figure 3 As shown, different coating ratios K of Examples 1-5 are given. 2 TiF 6 :Mn 4+ @KMgF 3 The XRD spectrum of the phosphor shows:

[0101] Uncoated K 2 TiF 6 :Mn 4+ With K 2 TiF 6 The standard PDF#08-0488 corresponds well.

[0102] After coating, as shown in the rectangular box in the figure, KMgF appears at diffraction angles of 31.63° and 45.42°. 3 The characteristic peaks of KMgF 3 The main peaks of the standard PDF#18-1033 are consistent, corresponding to KMgF 3 The (110) and (200) crystal planes. 2 TiF 6 :Mn 4 + With Mg 2+ As the molar ratio increases from 0.2 to 1.0, the relative peak intensity of the characteristic peak gradually increases, indicating that the coating thickness increases, but K 2 TiF 6 :Mn 4+ The main peak did not shift, indicating that KMgF 3 The generation of K does not affect 2 TiF 6 Basic structure.

[0103] like Figure 4 , 5 As shown, different coating ratios K of Examples 1-5 are given. 2 TiF 6 :Mn 4+ @KMgF 3 The emission spectrum and excitation spectrum of the phosphor after being immersed in water for 24 hours show that: as the coating ratio gradually increases, K 2 TiF 6 :Mn 4+@xKMgF 3 The luminous intensity of the phosphor gradually decreases.

[0104] As shown in Table 1, Figure 4 The relative peak intensity and relative integrated intensity of the emission spectrum. As shown in Table 1, when the coating ratio is 0.2, the relative peak intensity is the same as that of the uncoated K 2 TiF 6 :Mn 4+ The closest is 99.24%. When the coating ratio increases to 1.0, the peak intensity is 90.7% of the initial phosphor. Therefore, by using the surface modification scheme provided by the present invention, the moisture resistance of the phosphor can reach up to 99.24%, and the luminescence performance of the initial phosphor is almost not reduced.

[0105] Table 1

[0106] Covering ratio 0 0.2 0.4 0.6 0.8 1.0 Peak Intensity 276.2 274.1 273.1 258.1 257.9 250.5 Integral Strength 3023.157 3033.092 3010.387 2862.833 2854.629 2784.897

[0107] Embodiment 6-9

[0108] Examples 6-9 respectively provide a moisture-resistant fluoride red phosphor

[0109] K 2 TiF 6 :Mn 4+ @KMgF 3 ,

[0110] The difference between Example 6-9 and Example 1 is that: Step S4 is to coat the surface with KMgF 3 K 2 TiF 6 :Mn 4+ The core-shell structure fluoride red phosphor was immersed in water for 12 h, 36 h, 48 h and 60 h respectively.

[0111] like Figure 6 As shown, different soaking times K of Examples 1, 6-9 are given. 2 TiF 6 :Mn 4+ @KMgF 3 From the XRD spectrum of the phosphor, we can see that the relative peak intensity of the characteristic peaks at diffraction angles of 31.63° and 45.42° does not decrease significantly with the increase of immersion time, indicating that KMgF 3 The solubility of the shell is very low and it is easy to recrystallize.

[0112] like Figure 7 (a), (c), (e), and (g) show the uncoated K of Example 1, respectively. 2 TiF 6 :Mn 4+SEM image of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 SEM image of K of Example 1 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 SEM image of K of Example 1 after immersion in water for 60 hours 2 TiF 6 :Mn 4+ @KMgF 3 From the SEM image, we can see:

[0113] Uncoated K 2 TiF 6 :Mn 4+ The surface morphology is regular and smooth;

[0114] K after coating but not immersed in water 2 TiF 6 :Mn 4+ @KMgF 3 Irregular surface;

[0115] K after 24-hour and 60-hour immersion in water 2 TiF 6 :Mn 4+ @KMgF 3 The surface of the particles gradually becomes regular and flat, Figure 1 The change in the surface morphology of the phosphor particles corresponds to the change in the surface morphology of the phosphor particles.

[0116] like Figure 7 (b), (d), (f), and (h) show the uncoated K of Example 1, respectively. 2 TiF 6 :Mn 4+ EDS spectrum of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 EDS spectrum of Example 1 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 EDS spectrum and K of Example 1 immersed in water for 60 hours 2 TiF 6 :Mn 4+ @KMgF 3 From the EDS spectrum, we can see:

[0117] There is no Mg signal on the particle surface when not coated;

[0118] After coating and soaking in water for a certain period of time, there are Mg signals. Figure 1 , KMgF 3 It grows on the surface of phosphor.

[0119] like Figure 8 , 9 As shown, different soaking times K of Examples 1, 6-9 are given. 2 TiF 6 :Mn 4+ @KMgF 3 From the emission spectrum and excitation spectrum of the phosphor, we can see that: with the increase of immersion time, the relative peak intensity and relative integrated intensity of the emission spectrum gradually increase, reaching the highest after immersion for 24 hours, and then gradually stabilize and no longer increase or decrease. Figure 7 The SEM images of the coated phosphors in (a), (c), (e), and (g) are shown in Figure 1. The SEM images of the coated phosphors in water for different time periods correspond to the SEM images of the K 2 TiF 6 :Mn 4+ @KMgF 3 The irregular surface morphology of the phosphor will affect the luminescence performance of the phosphor.

[0120] As shown in Table 2, Figure 8 Relative peak intensity and relative integrated intensity of emission spectrum. As shown in Table 2, when the immersion time is 0, the luminescence intensity is the lowest. After immersion in water for a certain period of time, the luminescence intensity gradually increases. This is because the KMgF 3 The shell layer recrystallizes in water, and the surface tends to be regular and flat. Finally, the luminescence intensity of the phosphor returns to the K level of the uncoated but moisture-resistant phosphor. 2 TiF 6 :Mn 4+ Phosphor is at the same level.

[0121] Table 2

[0122] time 0h 12h 24h 36h 48h 60h Peak Intensity 270.7 281 295.5 297.2 296.4 295 Integral Strength 3009.354 3111.815 3343.793 3299.313 3297.482 3278.201

[0123] As shown in Table 3, the uncoated K of Example 1 is given. 2 TiF 6 :Mn 4+ , K of Example 1 2 TiF 6 :Mn 4+ @KMgF 3 , K of Example 1 immersed in water for 24 hours 2 TiF 6:Mn 4+ @KMgF 3 The results show that the K 2 TiF 6 :Mn 4+ @KMgF 3 The external quantum efficiency is lower than that of the sample immersed in water for 24 hours. 2 TiF 6 :Mn 4+ @KMgF 3 The external quantum efficiency returned to the initial uncoated K 2 TiF 6 :Mn 4+ 94.8%.

[0124] Table 3

[0125] sample Internal quantum efficiency Absorption rate External quantum efficiency <![CDATA[K 2 TiF 6 :Mn 4+ ]]> 86.46% 72.56% 62.73% <![CDATA[K 2 TiF 6 :Mn 4+ @KMgF 3 ]]> 83.71% 70.81% 59.27% <![CDATA[K 2 TiF 6 :Mn 4+ @KMgF 3 - Soak for 24 hours]]> 83.48% 71.22% 59.47%

[0126] Examples 10-25

[0127] Examples 10-25 provide a moisture-resistant fluoride red phosphor.

[0128] K 2 TiF 6 :Mn 4+ @KMgF 3 ,

[0129] The difference between Examples 10-25 and Example 1 is that:

[0130] KF 2 Aqueous solution concentration, K 2 TiF 6 :Mn 4+ Input molar amount, Mg(NO 3 ) 2 Aqueous solution concentration, Mg(NO 3 ) 2 The aqueous solution dropping rate and stirring speed are different, as shown in Table 5.

[0131] Examples 10-25 used Qualitek-4 orthogonal experiment analysis software to design a five-factor four-level orthogonal experiment, as shown in Table 4, which provides the parameter design range.

[0132] Table 4

[0133]

[0134]

[0135] In order to ensure the accuracy of the experimental results, two experiments were conducted. Fig.10 , 11 The emission spectra of samples 10-17 and 18-25 of the first orthogonal experiment are given respectively; Fig.12 , 13 The emission spectra of samples of Examples 10-17 and 18-25 of the second orthogonal experiment are given respectively; the average integrated intensity of the results of the two orthogonal experiments is given in Table 5.

[0136] As shown in Table 6, the average statistical analysis results of the average integrated intensity were performed using Qualitek-4 orthogonal experimental analysis software, specifically:

[0137] Best KHF 2 The solution concentration is 2 mol / L corresponding to level 3;

[0138] Best K 2 TiF 6 :Mn 4+ The molar amount of phosphor input is 0.01 mol corresponding to level 3;

[0139] The optimal magnesium nitrate solution concentration was 1 mol / L corresponding to level 2;

[0140] The optimal dripping rate is 60s / drop corresponding to level 3;

[0141] The optimal stirring speed is 50 r / min corresponding to level 1. The stirring speed factor has a low influence, with a contribution rate of 2.8% (49.868 / 1780.729). Considering the uniformity of the solution system during the reaction, subsequent experiments were carried out at a stirring rate of 400 r / min.

[0142] Table 5

[0143]

[0144]

[0145] Table 6

[0146]

[0147]

[0148] Embodiment 26

[0149] This embodiment provides a moisture-resistant fluoride red phosphor, K 2 SiF 6 :Mn 4+ @KMgF 3 ,

[0150] The fluoride red phosphor has a core-shell structure;

[0151] K 2 SiF 6 :Mn 4+ , where Mn 4+ The doping concentration is x = 0.08;

[0152] Shell is KMgF 3 .

[0153] The molar ratio of the shell to the core (coating ratio) is 0.2.

[0154] The preparation method of the moisture-resistant fluoride red phosphor of this embodiment is the same as that of Embodiment 1.

[0155] Examples 27-30

[0156] Examples 27-30 provide a moisture-resistant fluoride red phosphor.

[0157] K 2 SiF 6 :Mn 4+ @KMgF 3 ,

[0158] The difference between Examples 27-30 and Example 26 is that the shell KMgF 3 With nuclear K 2 SiF 6 :Mn 4+ The molar ratios (coating ratios) are 0.4, 0.6, 0.8, and 1.0, respectively.

[0159] like Fig.14 As shown, different coating ratios K of Examples 26-30 are given. 2 SiF 6 :Mn 4+ @KMgF 3 The XRD spectrum of the phosphor shows:

[0160] Uncoated K 2 SiF 6 :Mn 4+ With K 2 SiF 6 The standard PDF#75-0694 corresponds well.

[0161] After coating, as shown in the rectangular box in the figure, KMgF appears at diffraction angles of 31.63° and 45.42°. 3 The characteristic peaks of KMgF 3 The main peaks of the standard PDF#18-1033 are consistent, corresponding to KMgF 3 The (110) and (200) crystal planes. 2SiF 6 :Mn 4 + With Mg 2+ As the molar ratio increases from 0.2 to 1.0, the relative peak intensity of the characteristic peak gradually increases, indicating that the coating thickness increases, but K 2 SiF 6 :Mn 4+ The main peak did not shift, indicating that KMgF 3 The generation of K does not affect 2 SiF 6 Basic structure.

[0162] like Fig.15 (a)-(f) show the uncoated K of Example 26, respectively. 2 SiF 6 :Mn 4+ SEM images ((a)-(b)), K of Example 26 2 SiF 6 :Mn 4+ @KMgF 3 SEM images ((c)-(d)), K of Example 26 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 From the SEM images ((e)-(f)), we can see:

[0163] Fig.15 (a)-(b), uncoated K 2 SiF 6 :Mn 4+ The surface is relatively smooth, and the phosphor particles are uniformly square;

[0164] Fig.15 (c)-(d), K 2 SiF 6 :Mn 4+ @KMgF 3 The surface is covered with an uneven shell layer, and the particle surface is rough, but it can still be seen that the matrix is ​​a square phosphor particle;

[0165] Fig.15 (e)-(f), K of Example 26 immersed in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 The rough phosphor surface becomes relatively smooth.

[0166] like Fig.16 , 17As shown, different coating ratios K of Examples 26-30 are given. 2 SiF 6 :Mn 4+ @KMgF 3 From the emission spectrum and excitation spectrum of the phosphor after being immersed in water for 24 hours, it can be seen that the luminescence intensity of the phosphor after being coated and immersed in water for 24 hours is not significantly reduced compared with the untreated phosphor.

[0167] As shown in Table 7, Fig.16 The relative peak intensity and relative integrated intensity of the emission spectrum. As shown in Table 7, the results are consistent with K 2 TiF 6 :Mn 4+ The luminous intensity changes after coating are consistent. As the coating ratio increases, the luminous intensity gradually decreases. When x = 0.2, K 2 SiF 6 :Mn 4+ @0.2KMgF 3 The integrated intensity of the emission spectrum is the initial K 2 SiF 6 :Mn 4+ 96.15% of x = 1.0, that is, when the coating ratio is the largest and the shell is the thickest, K 2 SiF 6 :Mn 4+ @1.0KMgF 3 The integrated intensity of the emission spectrum is the initial K 2 SiF 6 :Mn 4+ 87.38%.

[0168] Table 7

[0169] Covering ratio 0 0.2 0.4 0.6 0.8 1.0 Peak Intensity 427.4 411.5 404.5 388.1 387.3 376 Integral strength 4045.89 3890.19 3832.42 3668.92 3669.51 3535.22

[0170] Embodiment 31

[0171] This embodiment provides a moisture-resistant fluoride red phosphor, K 2 TiF 6 :Mn 4+ @NaMgF 3 ,

[0172] The fluoride red phosphor has a core-shell structure;

[0173] K 2 TiF 6 :Mn 4+ , the same as in Example 1;

[0174] Shell is NaMgF 3 .

[0175] The molar ratio of the shell to the core (coating ratio) is 0.2.

[0176] The preparation method of the moisture-resistant fluoride red phosphor of this embodiment is the same as that of Embodiment 1.

[0177] Examples 32-35

[0178] Examples 32-35 provide a moisture-resistant fluoride red phosphor.

[0179] K 2 TiF 6 :Mn 4+ @NaMgF 3 ,

[0180] The difference between Examples 32-35 and Example 31 is that the shell NaMgF 3 With nuclear K 2 TiF 6 :Mn 4+ The molar ratios (coating ratios) are 0.4, 0.6, 0.8, and 1.0, respectively.

[0181] like Fig.18 As shown, different coating ratios K of Examples 31-35 are given. 2 TiF 6 :Mn 4+ @NaMgF 3 The XRD spectrum of the phosphor shows:

[0182] K 2 TiF 6 :Mn 4+ @NaMgF 3 Diffraction results and K 2 TiF 6 The standard PDF card corresponds accurately, and NaMgF appears at a diffraction angle of 47.3° 3 The characteristic peaks correspond exactly to the strongest peaks of the standard PDF card, indicating that the coating method successfully synthesized NaMgF 3 , and form a shell.

[0183] like Fig.19 , 20 As shown, different coating ratios K of Examples 31-35 are given. 2 TiF 6 :Mn 4+ @NaMgF 3 The emission spectrum and excitation spectrum of the phosphor after being immersed in water for 24 hours show that: as the coating ratio increases, the luminescence intensity gradually decreases. When x = 0.2, the integrated intensity is the initial K 2 TiF6 :Mn 4+ 74.3%, the waterproof performance is slightly lower than KMgF 3 Shell, when x = 0.8, the peak intensity is the initial K 2 TiF 6 :Mn 4+ 61.5%.

[0184] As shown in Table 8, Fig.19 Relative peak intensity and relative integrated intensity of the emission spectrum.

[0185] Table 8

[0186]

[0187]

[0188] Embodiment 36

[0189] This embodiment provides a white light LED device used as a display backlight source, the white light LED device includes a red light part, a green light part and a blue light part;

[0190] The red light portion is the moisture-resistant fluoride red phosphor described in Example 1;

[0191] The green light part is β-SIALON green powder;

[0192] The blue light part is an InGaN blue light chip.

[0193] like Fig.21 (a) shows the K of Example 1. 2 TiF 6 :Mn 4+ @KMgF 3 Packaged white LED spectra and devices, such as Fig.21 (b) shows a comparison diagram of the CIE color gamut diagram of the white light LED device of this embodiment and the standard color gamut diagram of the National Standards Television Committee. Fig.21 As shown in (a) and (b), the color gamut of the white light LED device of this embodiment reaches 105.2% NTSC, and the luminous efficiency is 97.55 lm / W, which is suitable as a display backlight source.

[0194] like Fig. 22 , 23 As shown, K 2 TiF 6 :Mn 4+ (①), K 2 TiF 6 :Mn 4+ @KMgF 3However, K after not soaking in water (②) and after soaking in water for 24 hours 2 TiF 6 :Mn 4+ @KMgF 3 (③) The thermal steady-state luminous flux attenuation curve and thermal steady-state voltage attenuation curve of the packaged white light LED device show that device No. ③ has the best stability under the double 85 test conditions. After 360 seconds of testing, the luminous flux attenuation is 90.55% and the device voltage is 99.13%, which is significantly smaller than the attenuation of device No. ①.

[0195] As shown in Table 9, the photoelectric parameters of devices ①, ② and ③ under 120mA current excitation are shown.

[0196] Table 9

[0197] serial number Light efficiency (Lm / W) Color gamut (NTSC) Luminous efficiency (%) ① 93.05 105.2% 47.6 ② 89.46 105.2% 38.9 ③ 97.55 105.2% 46.8

[0198] Comparative Example 1-2

[0199] Comparative Examples 1-2 respectively use alkaline earth metal nitrate solutions of the same family as Mg, Ca 2+ and Sr 2+ , replacing Mg(NO 3 ) 2 The aqueous solution was dripped into the mixed solution for coating treatment, and the other steps were the same as those in Example 1. Figure 24-26 As shown:

[0200] The coated phosphors show obvious characteristic peaks of shell materials at the corresponding diffraction angles.

[0201] Fig.24 It can be seen that the surface coated KMgF 3 K 2 TiF 6 :Mn 4+ The XRD pattern of the core-shell fluoride red phosphor shows KMgF at diffraction angles of 31.63° and 45.42°. 3 Characteristic peaks of

[0202] Fig.25 It can be seen that CaF appears at diffraction angles of 28.27° and 47.00° 2 Characteristic peaks of

[0203] Fig.26 It can be seen that SrF appears at diffraction angles of 26.57° and 44.12° 2 characteristic peaks.

[0204] This indicates that the same coating process is used, and different alkaline earth metal nitrates are used as titration solutions. Only Mg 2+The addition of nitrate solution will generate KMgF 3 .

[0205] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a moisture-resistant fluoride red phosphor, characterized in that: The fluoride red phosphor has a core-shell structure; Core is Mn 4+ Doped fluoride red phosphor, chemical formula A2B 1-x F6:xMn 4+ , wherein A is at least one of Li, Na, K, Rb and Cs, B is at least one of Ti, Si, Ge, Zr and Sn, 0<x≤0.4; The shell is a cubic perovskite compound with a chemical formula of CMgF3, wherein C is at least one of Li, Na, K, Rb and Cs. The method comprises the following steps: S1: preparing a CHF2 aqueous solution and a Mg(NO3)2 aqueous solution, wherein C is at least one of Li, Na, K, Rb and Cs; S2: The Mn 4+ The doped fluoride red phosphor is mixed and stirred evenly with the CHF2 aqueous solution to obtain a mixed solution; S3: Continue stirring the mixed solution, drip the Mg(NO3)2 aqueous solution into the mixed solution, and after the dripping is completed, stir, separate the solid and liquid, wash and dry in sequence to obtain A2B coated with CMgF3 on the surface. 1-x F6:xMn 4+ Core-shell structure fluoride red phosphor; S4: The surface of the A2B coated with CMgF3 1-x F6:xMn 4+ The core-shell structure fluoride red phosphor is immersed in water, and subjected to solid-liquid separation, washing and drying to obtain the moisture-resistant fluoride red phosphor.

2. The method for preparing the moisture-resistant fluoride red phosphor according to claim 1, wherein: The molar ratio of the shell to the core is 0.005-1.

0.

3. The method for preparing the moisture-resistant fluoride red phosphor according to claim 1, wherein: The molar concentration of the CHF2 aqueous solution is 0.001-10 mol / L; The molar concentration of the Mg(NO3)2 aqueous solution is 0.001-10 mol / L; The CHF2 aqueous solution, the Mg(NO3)2 aqueous solution and the Mn 4+ The dosage ratio of the doped fluoride red phosphor is (0.01-30)L: (0.01-10)L: 1g; The Mn 4+ The molar amount of the doped fluoride red phosphor is 0.001-0.40 mol.

4. The method for preparing the moisture-resistant fluoride red phosphor according to claim 1, wherein: In step S2, the stirring rate is 50-1200 rpm, and the stirring time is 0-60 min.

5. The method for preparing the moisture-resistant fluoride red phosphor according to claim 1, wherein: In step S3, The stirring rate for continuous stirring is 50-1200 rpm; The stirring rate after the dripping is 50-1200rpm, and the stirring time is 0-60min; The dripping rate is 1-90 seconds / drop.

6. The method for preparing the moisture-resistant fluoride red phosphor according to claim 1, wherein: In step S4, the soaking time is 1-60 hours.

7. Application of the moisture-resistant fluoride red phosphor prepared by the method for preparing the moisture-resistant fluoride red phosphor according to any one of claims 1 to 6 in the red light portion of white light LED devices used as display backlight sources and high color rendering and high contrast lighting sources.

8. A white light LED device used as a display backlight source and a high color rendering and high contrast lighting source, characterized in that: The white light LED device includes a red light part, a green light part and a blue light part; The red light portion is a moisture-resistant fluoride red phosphor prepared by the method for preparing a moisture-resistant fluoride red phosphor according to any one of claims 1 to 6.

9. The white light LED device according to claim 8, wherein: The green light part is a green phosphor with an emission wavelength peak of 520-560nm and a half-width not exceeding 35nm; the blue light part is an InGaN blue light chip.

Citation Information

Patent Citations

  • Processes for preparing color stable red-emitting phosphor particles having small particle size

    CN110546237A